Cell-Type-Specific Cytokinin Distribution within the Arabidopsis Primary Root Apex - Antoniadi, Ioanna; Plačková, Lenka; Simonovik, Biljana; Doležal, Karel; Turnbull, Colin; Ljung, Karin; Novák, Ondřej (The Plant cell, 2015)
Cytokinins (CKs) play a crucial role in many physiological and developmental processes at the levels of individual plant components (cells, tissues, and organs) and by coordinating activities across these parts. High-resolution measurements of intracellular CKs in different plant tissues can therefore provide insights into their metabolism and mode of action. Here, we applied fluorescence-activated cell sorting of green fluorescent protein (GFP)-marked cell types, combined with solid-phase microextraction and an ultra-high-sensitivity mass spectrometry (MS) method for analysis of CK biosynthesis and homeostasis at cellular resolution. This method was validated by series of control experiments, establishing that protoplast isolation and cell sorting procedures did not greatly alter endogenous CK levels. The MS-based method facilitated the quantification of all the well known CK isoprenoid metabolites in four different transgenic Arabidopsis thaliana lines expressing GFP in specific cell populations within the primary root apex. Our results revealed the presence of a CK gradient within the Arabidopsis root tip, with a concentration maximum in the lateral root cap, columella, columella initials, and quiescent center cells. This distribution, when compared with previously published auxin gradients, implies that the well known antagonistic interactions between the two hormone groups are cell type specific.
Keywords: Arabidopsis; separace buněk; Organ Specificity; Plant Roots; kyseliny indoloctové; miniaturizace; meristém; Miniaturization; Protoplasts; Flow Cytometry; Cytokinins; kořeny rostlin; Meristem; cytokininy; extrakce na pevné fázi; biologický transport; zelené fluorescenční proteiny; průtoková cytometrie; protoplasty; Indoleacetic Acids; Cell Separation; Green Fluorescent Proteins; Metabolome; metabolom; orgánová specificita; Solid Phase Extraction; Biological Transport